Peran Pemerintah Kota Malang dalam Membangun Inovasi Digital Marketing UKM Industri Kreatif Kriya - Siti Munfaqiroh (Mahesa Research Center, 2023)
This study aims to analyze the role of the Malang City government in building digital marketing innovations for SMEs in the creative craft industry. Innovation in digital marketing in Indonesia continues to grow along with changing trends and market needs, including the craft creative industry. In addition to the cities of Bandung, Bali and Yogyakarta which are known for their craft creative industry SMEs, Malang City is also one of the important cities in Indonesia in the craft creative industry SMEs. To examine more deeply the role of the Malang City Government, descriptive qualitative research methods are used. Descriptive qualitative research methods include the use of observation, interviews, case studies, or document analysis. The collected data is then systematically analyzed and interpreted to describe and explain the observed phenomena. The results show, in addition to being supported by the ecosystem, demography, geography and tourism in Malang City, the Malang city government also has a significant role in efforts to Build Digital Marketing Innovation for SMEs in the Creative Industry Kriya. This can be seen from holding a Technical Workshop on Creative Craft and Fashion Industries for Small and Medium Industries (IKM), and the construction of the Malang Creative Facility (MCC) Building located on Jalan Ahmad Yani Utara Malang City, East Java, used as an incubation facility for Micro, Small and Medium Enterprises (UMKM) and the creative economy sector.